2015
DOI: 10.14260/jemds/2015/2318
|View full text |Cite
|
Sign up to set email alerts
|

Operative Management of Intra - Articular Distal Humeral Fractures With Locking Plates

Abstract: BACKGROUND: Intra-articular distal humeral fractures are common, but complex elbow injuries. To obtain good results, anatomical reduction with rigid fixation and early range of mobilization is required. Treatment of these fractures with conventional plates is associated with many complications such as non-anatomic reduction of articular surfaces, malunion, nonunion, loosening of implant, residual stiffness of the elbow and post-traumatic osteoarthrosis. In this situation the application of locking plates havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…These finding were consistent with other studies. We had no ulnar neuropraxia, and heterotrophic ossification complication which were reported in other studies by Mishra et al, Singh et al, Kaiser et al [3][4][5][6][7][8][9][10] Functional evaluation was done with mayo elbow performance score in our study. Results were excellent and good in 83% of patients, fair (10%) and poor (7%).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…These finding were consistent with other studies. We had no ulnar neuropraxia, and heterotrophic ossification complication which were reported in other studies by Mishra et al, Singh et al, Kaiser et al [3][4][5][6][7][8][9][10] Functional evaluation was done with mayo elbow performance score in our study. Results were excellent and good in 83% of patients, fair (10%) and poor (7%).…”
Section: Discussionsupporting
confidence: 57%
“…Average age of patients in our study was 37.5 years which is comparable with other studies 36 years by Mishra et al, 37.5 years by Singh et al, and 38.4 by Gupta et al years. [3][4][5] We found male population affected more in our study, i.e., active working population. This is in consistence with other studies like 66.7% by Atalar et al and 60% by Lakhey et al 6,7 Mode of injury in our study was road traffic accident which differs from other studies like fall in Li et al and Muzaffar et al studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The resultant mean range of elbow motion was 116 degrees at the final follow up, which nearly identical with the study by Imran mang et al (2014) [18] where they achieved mean elbow range of motion of 110. Abilhek Mishra [24] et al in their study complication rate was 15% with 2 (10%) cases of transient ulnar neuropraxia and 1(5%) case of superficial infection. Muzaffar N et al (2014) [21] in their study encountered 4(16%) cases of superficial infection; 1(4%) case of Ulnar neuropraxia 2(8%) had metal prominence (olecranon K-wires).…”
Section: Discussionmentioning
confidence: 87%
“…In our study there were 15(75%) males and 5(25%) females, which is comparable with the studies conducted by Kiran G U et al 107 and Riyaz sheik et al109 which showed 14 (70%) males and 6(30%) females and also with the study conducted by Ata Can Atalar et al72 which showed 14 (66.67%) males and 7(33.33%) females In our study excellent results were found in 75%, good results in 15%, fair in 5% and poor results in 5% cases. Abilhekh Mishra et al [16] in their study of 20 patients found the results as excellent in 15(75%), good in 3(15%), fair in 1(5%) and poor in 1(5%) Imran mang et al [13] in their study of 25 patients found excellent results in 12(48%), good in 8(32%), fair in 3(12%) and poor in 2(8%) Singh V. [15] et al 106 in their study of 27 patients found the results as excellent in 4(14.81%), good in 13(48.14%), fair in 7(25.9%) and poor in 3(11.11%) Our study is closely comparable with these above mentioned studies.…”
Section: Sex Distributionmentioning
confidence: 99%